Social Advocacy: The Role of the Primary Health Care (PHC) Nurse as a Community Partner and Enabler of Community Self- Empowerment. - Agbedia Clara; Aikabeli Priscilla (International Journal of Educational Excellence and Innovation, 2025)
Advocacy, empowerment and consumerism are popular concepts that permeate today’s health agenda especially with the paradigm shift from a seemingly professional-led service to a user-led service. Nurses, over the years, have intuitively seen themselves as patient advocates, as they mediate between patient and community resources, between patient and medical services and between patient and family. This paper explores the many ways that the nurse can safeguard the interest of individual patients in health care.